2020
DOI: 10.3390/ijms21113928
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria: A Galaxy in the Hematopoietic and Leukemic Stem Cell Universe

Abstract: Mitochondria are the main fascinating energetic source into the cells. Their number, shape, and dynamism are controlled by the cell’s type and current behavior. The perturbation of the mitochondrial inward system via stress response and/or oncogenic insults could activate several trafficking molecular mechanisms with the intention to solve the problem. In this review, we aimed to clarify the crucial pathways in the mitochondrial system, dissecting the different metabolic defects, with a special emphasis on hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 209 publications
1
29
0
Order By: Relevance
“…Immuno-reactive bands were visualized by using chemiluminescent enhanced reagent (Clarity Western ECL Substrate #170-5061, Bio-Rad). Quantification was performed using the Image Lab program (BioRad Laboratories, Hercules, CA, USA) [ 87 ].…”
Section: Methodsmentioning
confidence: 99%
“…Immuno-reactive bands were visualized by using chemiluminescent enhanced reagent (Clarity Western ECL Substrate #170-5061, Bio-Rad). Quantification was performed using the Image Lab program (BioRad Laboratories, Hercules, CA, USA) [ 87 ].…”
Section: Methodsmentioning
confidence: 99%
“…Modulating ATP availability might be an essential strategy in inducing cell resistance and sustaining cancer progression and growth (4). Recent findings have demonstrated that cancer cells take advantage of high OXPHOS, including leukemias, lymphomas, pancreatic ductal adenocarcinoma, melanoma, and endometrial carcinoma (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), while mitochondria can modulate their morphology regulating the intrinsic apoptotic pathway and participating in the resistance of cancer cells to apoptotic stimuli (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The change in MMP was highest for NCI-H520, while NCI-446 and A549 displayed smaller changes, consistent with the results of the cytotoxic effects of LIP on the three tumor cell lines. The results of the ROS experiment further confirmed tumor cell apoptosis ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 58%